PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP PERPUTARAN TENAGA KERJA DEPARTEMEN FOOD AND BEVERAGE SERVICE DI HOTEL HILTON BALI - Rizky Witasari (STIE BIITM, 2020)
This study aimed to examine the effect of Individual Characteristics (X1), JobCharacteristics (X2) and Labor Turnover (Y). The population in this research is anemployees food and beverage service department at Hilton Hotel Bali. The samples in thisresearch were 60 employees using slovin method. The methods of data collection usinginterview and questionnaires. To analyzing data using percentage of multiple linearregression analysis using SPSS. Based on the research results, there is evident that thesignificant partially individual characteristics and job characteristics toward labor turnoverfood and beverage service department at Hilton Hotel Bali. Based on the t test, individualcharacteristics sig 0.000 and job characteristics sig 0.004 to labor turnover < 0.05 than asignificant to performance H1 and H2 received. The study concluded there was a significantpositive effect of individual characteristics and job characteristics to labor turnover food andbeverage service department at Hilton Hotel Bali. Suggestions for the company shouldprovide a decent pay rise, place the employee in accordance with the expertise. For otherresearchers can add objects and other variables.